Vision Versus Reality: Testing Methods to Study Public Space Design and Pedestrian Experience in Logan Central - Marnane, Kali; Shaweesh, Maram (Urban Planning and Construction, 2025)
Logan is a rapidly growing, mid-sized city in Queensland, Australia, often characterized by low-density suburban development, car dependency, and persistent socio-economic disadvantage. Logan Central, identified as the civic and cultural heart of the city, faces compounded challenges related to disconnected pedestrian infrastructure, fragmented public spaces, and negative public perception. This paper reports on a preliminary public space–public life study conducted in August 2022 across five locations in Logan Central. The study aimed to test the applicability of observational and participatory methods in revealing how public space is occupied, navigated, and experienced. Guided by a critical urban framework grounded in the right to the city, spatial justice, the politics of mobility, and everyday urbanism, the study demonstrates how lived experiences of space—particularly those of young people and small business owners—offer powerful insights into inclusion, access, and urban vibrancy. Two key opportunities emerged: the catalytic role of local businesses and events in activating space, and the untapped potential of young pedestrians in shaping public life. These findings challenge dominant deficit narratives and show how a micro-scale, people-centered approach can support more equitable planning and design. The study is intended as a methodological pilot to inform future longitudinal research, teaching, and planning efforts, offering a scalable approach to tracking spatial justice and pedestrian experience over time in Logan and comparable suburban contexts.